A Case of Wolfram Syndrome - Gholamali Naderian; Fereshteh Ashtari; Kia Nouri-Mahdavi; Valleh Sajjadi (Journal of Ophthalmic & Vision Research, 2010)
Purpose: To report a case of Wolfram syndrome characterized by early onset diabetes mellitus and progressive optic atrophy. Case Report: A 20-year-old male patient with diabetes mellitus type I presented with best corrected visual acuity of 1/10 in both eyes with correction of -0.25+1.50@55 and -0.25+1.50@131 in his right and left eyes, respectively. Bilateral optic atrophy was evident on fundus examination. The patient also had diabetes insipidus, neurosensory deafness, neurogenic bladder, polyuria and extra-residual voiding indicating atony of the urinary tract, combined with delayed sexual maturity. Conclusion: One should consider Wolfram syndrome in patients with juvenile onset diabetes mellitus and hearing loss. Ophthalmological examination may disclose optic atrophy; urologic examinations are vital in such patients.